2008
DOI: 10.1590/s1516-84842008000300011
|View full text |Cite
|
Sign up to set email alerts
|

Importância dos testes sorológicos de triagem e confirmatórios na detecção de doadores de sangue infectados pelo vírus da hepatite C

Abstract: Correspondência: Helio Moraes de Souza Av. Getúlio Guarita, 3312-5077 E-mail: helio.moraes@hemominas.mg.gov.br Artigo / Article REVISTA BRASILEIRA DE HEMATOLOGIA E H E M O T E R A P I A IntroduçãoO teste para detecção de anti-HCV tornou-se obrigató-rio na triagem sorológica dos bancos de sangue brasileiros em novembro de 1993.1 Alguns hemocentros introduziramno mais precocemente, como a Fundação Hemominas, que introduziu-o em sua rotina em 1992.2 Desde então, o aperfeiçoamento das técnicas e o desenvolvim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 11 publications
0
3
0
8
Order By: Relevance
“…The total length of sample collection was seven months. After selection, the participants underwent the following steps: a) approach, called the pre-test, in which the counseling premises contained in the Handbook of Viral Hepatitis Counseling of the Ministry of Health 13 14 ; e) examination results, called post-test, the moment the researchers had the opportunity to clarify any doubts; f ) after a negative result, this was noted on the completed form and the participants were released with a copy of the printed report; g) in the event of the occurrence of a positive result the subjects were immediately scheduled in the Municipal STD/AIDS and Hepatitis Program to confirm the diagnosis and for subsequent treatment according to the clinical criteria proposed by the Clinical Protocol and Thera- 16 . In this study, confirmation was made by means of the third generation enzyme immunoassay (EIA), or ELISA--III, which detects antibodies directed against several epitopes of the C virus located in the capsid.…”
Section: Methodsmentioning
confidence: 99%
“…The total length of sample collection was seven months. After selection, the participants underwent the following steps: a) approach, called the pre-test, in which the counseling premises contained in the Handbook of Viral Hepatitis Counseling of the Ministry of Health 13 14 ; e) examination results, called post-test, the moment the researchers had the opportunity to clarify any doubts; f ) after a negative result, this was noted on the completed form and the participants were released with a copy of the printed report; g) in the event of the occurrence of a positive result the subjects were immediately scheduled in the Municipal STD/AIDS and Hepatitis Program to confirm the diagnosis and for subsequent treatment according to the clinical criteria proposed by the Clinical Protocol and Thera- 16 . In this study, confirmation was made by means of the third generation enzyme immunoassay (EIA), or ELISA--III, which detects antibodies directed against several epitopes of the C virus located in the capsid.…”
Section: Methodsmentioning
confidence: 99%
“…All blood donors with a positive or indeterminate enzyme-linked immunosorbent assay (ELISA) anti-hCV test (third and fourth generation) who were seen at the uberaba regional Blood Center between November 1992 and December 2005 were studied, as explained in a previous paper 6 . The donors were first divided into first-time donors and repeat donors.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that with the new technique, the 'immunological window' is reduced from 22 to 10 days for HIV infections and from 90 to 15 days for HCV infections. Studies carried out in the HRU in 2008 and in a blood bank in São Paulo in 2004 also support the implementation of this method (19,20) . A work published in 2011 also defends the use of increasingly sensitivity and specific serological screening methods in an attempt to increase transfusion safety (21) .…”
Section: Discussionmentioning
confidence: 86%